Determining Internal and External Risks in a Medical Center - Alexander, Cheryl Ann; Wang, Lidong (International Journal of Criminology and Sociology, 2025)
An enterprise stores information in the cloud providing virtual storage of data as virtual memory. Cloud increases the enterprise’s ability to offer data and service delivery, however it also increases the chances of a cybersecurity threat, and cyber risks, and increases the vulnerability of the enterprise to risks. It is important for the organization to perform risk management to determine cybersecurity risks. Cybersecurity is a key need for hospitals to manage threats of all types. Healthcare is notoriously vulnerable to cyber-attacks due to the valuable nature of patient information and the lack of updated medical equipment. In this paper, we discuss medical applications in cybersecurity, AI’s role in cybersecurity, and risk management in medical cybersecurity.